Application of the Service Reply System to Increase Work Productivity of Statistics Office Officers in Bantaeng Regency - Amir, Ali Syahban (Universitas Negeri Makassar, 2019)
This study aims to look at the forms of work motivation that are applied in increasing the productivity of employees of the Bantaeng Regency Statistics Office, and to determine the factors that influence employee motivation. This type of research is a case study with the reason that this study is specific to clearly describe the meaning or phenomenon that occurs. This study also uses the naturalistic paradigm approach (qualitative) to analyze and construct employees who are directed to obtain data based on empirical facts. Data analysis was carried out by data reduction focused on selecting, simplifying, abstracting and transforming crude data from field notes, followed by data presentation and conclusion drawing. The results of this study indicate that the reciprocal system looks at the three indicators, namely: 1) Providing work motivation to employees through the level of well-being, 2) promotion and 3) the completeness of office facilities and infrastructure can produce increasing levels of productivity, giving motivation through promotion have a positive impact because employees have the ability to create effectiveness and efficiency in work, office facilities and infrastructure have undergone spontaneous changes, namely from manual to computerized systems.Â